Corpus alienum migrující cizí těleso - Sojka, L (Rozhledy v chirurgii, 2016)
Our case study presents a case of foreign body migration through the vascular system of the human body. The following paper is a comprehensive overview of different diagnostic approaches, extraction indications, common ways in which a foreign body can migrate via the vascular system and possible complications caused by the migration or extraction of the foreign body.
Keywords: arteria pulmonalis; Pulmonary Artery; počítačová rentgenová tomografie; migrace cizích těles; Foreign-Body Migration; Humans; následné studie; foreign object - extraction migration.; Follow-Up Studies; Tomography, X-Ray Computed; lidé